A pulse oximeter system, OxiSense, with embedded signal processing using an ultra-low power ASIC designed for testability. (February 2018) - Das, Devarshi Mrinal; Gupta, Aman; Srivastava, Abhishek; Vidwans, Amogh; Ahmad, Meraj; Shelke, Aniruddha; Kale, Salil; Ananthapadmanabhan, J.; Sharma, Dinesh Kumar; Baghini, Maryam Shojaei
Abstract: This paper presents a complete IoT enabled pulse oximeter (PO) system, called OxiSense, made using a custom designed low power application specific integrated circuit (ASIC) for signal conditioning. One of the novel aspects of the developed system is the testability of all the important modules of the ASIC (both analog and digital) using auxiliary circuits implemented in the ASIC. Another novel aspect is a new embedded and efficient signal processing algorithm which is robust to small motion artifacts. This new algorithm has been implemented on a low-power micro-controller (embedded processing mode) as well as on PC using Python (remote processing mode). The PO ASIC is fabricated in 180 nm mixed-mode CMOS technology and it works at 1.8 V supply voltage. The average power consumption of the analog front-end is 176 µW and that of the digital module controlling the analog front-end is 23 µW. The prototype PO system made using the custom ASIC operates from a 3.7 V lithium ion battery and consumes about 8 mW power. The prototype is housed in a 3D printed casing and it connects with a display device via USB or wirelessly to laptop/smartphone/tablet. Readings on 20 subjects, both in the lab and in hospital, show less than 2% deviation in the measured S p O 2 level and worst case deviation of 2.7 beats per minute for the measured heart rate, when compared with the commercial POs.